A genome-wide investigation of Mycoplasma hominis genes associated with gynecological infections or infertility - Chibani, Salim; Yacoub, Elhem; Boujemaa, Safa; Mardassi, Helmi; Guglielmini, Julien; Vaysse, Amaury; Khadraoui, Nadine; Mlik, Béhija; Ben Abdelmoumen Mardassi, Boutheina (Frontiers in Microbiology, 2025)
Background and aimMycoplasma hominis is a human pathogenic bacterium that causes a wide range of genital infections and reproductive issues. Previously, based on an extended multilocus sequence typing scheme, we provided evidence for the segregation of M. hominis clinical strains into two distinct pathotypes: gynecological infections or infertility. Here, based on whole genome sequencing (WGS) data, we sought to provide a more refined picture of the phylogenetic relationship between these two M. hominis pathotypes, with the aim to delineate the underlying genetic determinants.MethodsWe carried out WGS of 62 Tunisian M. hominis clinical strains collected over a 17-year period. The majority of these clinical strains are associated with infertility (n = 53) and the remaining nine isolates are from gynecological infections cases. An alignment-free distance-based procedure (Jolytree) was used to infer phylogenetic relationships among M. hominis isolates, while the phylogenetic method treeWAS was used to determine the statistical association between pathotypes of interest and genotypes at all loci.ResultsThe total pangenome of M. hominis strains was found to contain 1,590 genes including 966 core genes and 592 accessory genes, representing 60 and 37% of the total genome, respectively. Collectively, phylogenetic analyses based on WGS confirmed the distinction between the two M. hominis pathotypes. Strikingly, genome wide association analyses identified 4 virulence genes associated with gynecological infections, mainly involved in nucleotide salvage pathways and tolerance to oxidative stress, while five genes have been associated with infertility cases, two of which are implicated in biofilm formation.ConclusionIn sum, this study further established the categorization of M. hominis into two pathotypes, and led to the identification of the associated genetic loci, thus holding out promising prospects for a better understanding of the differential interaction of M. hominis with its host.